Integrative Functional Transcriptomic Analyses Implicate Shared Molecular Circuits in Sensorineural Hearing Loss - Chen, Peng; Hao, Jun-Jun; Li, Meng-Wen; Bai, Jing; Guo, Yuan-Ting; Liu, Zhen; Shi, Peng (Frontiers in Cellular Neuroscience, 2022)
Sensorineural hearing loss (SNHL) is referred to as the most common type of hearing loss and typically occurs when the inner ear or the auditory nerve is damaged. Aging, noise exposure, and ototoxic drugs represent three main causes of SNHL, leading to substantial similarities in pathophysiological characteristics of cochlear degeneration. Although the common molecular mechanisms are widely assumed to underlie these similarities, its validity lacks systematic examination. To address this question, we generated three SNHL mouse models from aging, noise exposure, and cisplatin ototoxicity. Through constructing gene coexpression networks for the cochlear transcriptome data across different hearing-damaged stages, the three SNHL mouse models are found to significantly correlate with each other in multiple gene coexpression modules that implicate distinct biological functions, including apoptosis, immune, inflammation, and ion transport. Bioinformatics analyses reveal several potential hub regulators, such as IL1B and CCL2, both of which are verified to contribute to apoptosis accompanied by the increase of reactive oxygen species (ROS) in in vitro model system. Our findings further disentangle the shared molecular circuits across different types of SNHL, providing potential targets for the broad effective therapeutic agents in SNHL.